Efeito da oxime (3z)-5-cloro-3-(hidroxiimino)-indolin-2-ona sobre a hepatotoxicidade e os distúrbios na homeostase da glicose induzidos pela intoxicação por organofosforado - Abreu, Edina da Luz (2019)
In this study, the effects of oxime, (3Z) -5-chloro-3- (hydroxyimino) indolin-2-one (OXIMA), of unprecedented syndrome, on disorders of glucose metabolism and non-dental malation, a organophosphate insecticide in rats. Adult males were divided into four groups: Control; Malation; OXIMA; and Malation + OXIMA. Free pain after concomitant treatment with malathion (250mg / kg, i.p.) and / or oxyme (50mg / kg, i.g.), plasma and fox were collected. A single dose of OXIMA decreased glycemia and hepatic glycogen content increased by malathion. In addition, OXIMA attenuated the increase in plasma markers of liver function (AST, ALT, ALP) and inhibited the enzyme catalase and glutathione reductase in the liver of rats with the association. In addition, inhibition of hepatic acetylcholinesterase induced by long-term treatment has been one of the main toxicity factors of organophosphates, was suppressed by treatment with OXIMA. Thus, results indicate that (3Z) -5-chloro-3- (hydroxyimino) indolin-2-one is a promising molecule and may be considered for other studies looking for novel alternatives without treatment of organophosphorus poisoning.